Case Report: Gastric and duodenal metastasis of malignant melanoma: a rare clinical presentation - Zheng, Huantian; Zhang, Weijian; Yang, Weiqin; Liu, Lingyun; Peng, Yu; Huang, Yanzi; Huang, Shaogang; Kang, Jianyuan; Lin, Baofu; Guo, Shaoju; Li, Haiwen (Frontiers in Oncology, 2025)
BackgroundMalignant melanoma represents one of the most common sources of metastatic tumors to the gastrointestinal (GI) tract. However, synchronous involvement of both the stomach and duodenum is exceptionally rare. Ante-mortem diagnosis remains challenging due to frequent asymptomatic or non-specific presentations. Endoscopically, metastases may present as ulcerated nodules, submucosal masses, or pigmented lesions, necessitating confirmation via immunohistochemical staining.ObjectiveThis case report describes a rare instance of synchronous gastric and duodenal metastases from malignant melanoma, aiming to enhance clinical awareness of this condition.MethodsWe present the case of a 67-year-old male with a history of wild-type BRAF V600E malignant melanoma of the left lower limb, status post resection three years prior, who presented for observation with known multi-system metastases. The patient reported decreased appetite but denied other GI symptoms. Upper gastrointestinal endoscopy was performed, revealing suspicious lesions in the stomach and duodenum, which were subsequently biopsied for histopathological and immunohistochemical analysis.ResultsEndoscopy identified a mass on the posterior wall of the gastric fundus and the greater curvature of the upper stomach, alongside four masses in the duodenal bulb. All lesions exhibited surface melanin deposition. Histological examination revealed tumor cells with prominent nucleoli and visible melanin granules. Immunohistochemistry was positive for S100, Melan-A, and SOX10, with a high Ki67 proliferation index of 90%, confirming the diagnosis of metastatic malignant melanoma.ConclusionThis case underscores the potential for malignant melanoma to develop synchronous metastases in both the stomach and duodenum, even in the absence of specific GI symptoms (3, 6). It highlights the critical role of endoscopic evaluation and immunohistochemical analysis in achieving a timely diagnosis (4, 7). A high index of suspicion is warranted in patients with a history of melanoma, as GI metastases confer a poor prognosis (4, 7).